A rare case of xanthogranuloma of the stomach masquerading as an advanced stage tumor - Arii Kazuo (World Journal of Surgical Oncology, 2011)
Abstract Background Xanthogranuloma of the stomach is an extremely rare disease, and this lesion has only been found to coexist with early gastric cancer in 2 cases in the literature. Case presentation We report a case of xanthogranuloma of the stomach combined with early gastric cancer that mimicked an advanced stage tumor. A 65-year-old female was referred to our hospital because of epigastralgia. During a physical examination, a defined abdominal mass was palpable in the region of the left hypochondrium. Imaging studies revealed an advanced gastric cancer, which was suspected of having infiltrated the abdominal wall. Total gastrectomy and resection of the regional lymph node and abdominal wall were performed. Histopathologic examination of the resected specimen demonstrated xanthogranuloma combined with early gastric cancer. Conclusion Xanthogranuloma presenting as a form of SMT (submucosal tumor) of the stomach is an extremely rare disease, and diagnosing it preoperatively is difficult. Further accumulation and investigation of this entity is necessary.